Influence of different blade vibration modes on fluid fluctuation in the tip vortex region: an experimental study. Issue 1 (31st March 2022) - Ma, Jianlong; Duan, Yafan; Zhao, Ming
ABSTRACT: Poor understanding of the fluid–structure interaction of a wind turbine blade is a well-known bottleneck in the development of the wind power industry. The degree to which different blade vibration modes influence the fluid fluctuation intensity and the manner of its variation with working conditions remain unknown, which restricts the understanding of fluid–structure interaction and the development of corresponding decoupling methods. To this end, an experiment for synchronously monitoring blade vibration parameters, near-wake flow parameters, and generator output parameters was conducted in the present study. To prevent impacting the characteristics of blade structure and wake flow, an indirect test for identifying the dynamic frequencies was developed. To validate this method, a small wind turbine was utilized to experimentally investigate the influence of different blade vibration modes on the fluid fluctuation in the tip vortex region. The results revealed that the blade vibrations have significant influences on the wake flow fluctuation. They also indicated the differences in the intensities of four types of low-frequency vibrations under static and dynamic conditions. Eventually, the relationship between the intensities of blade vibration modes and those of fluid fluctuation with varying blade rotation speeds was also analyzed.